(untitled) (Scientific journal of the Fergana State University, 2023)
This article is about the linguistic theories that reflect the etymological, functional, semantic, cognitive and comparative analysis of the existing reduplicative elements in the English language. The presence of reduplicative elements in the English language in various fields of linguistics is shown.